Caracterização e análise das comunidades e infracomunidades de parasitos metazoários de Plagioscion squamosissimus (Heckel, 1840) capturados no reservatório de Promissão, rio Tietê, estado de São Paulo - Lapera, Ivan Moura [UNESP] (2015)
The objective of this study was to characterize and analyze the communities and infracommunities of metazoan parasites of Plagioscion squamosissimus caught in Promissão reservoir, Tiete river in Borborema city (21°39′58S, 49°8′49W), São Paulo State. Fish were caught by professional fishermen on March 2015 and 50 specimens were examined. The obtained parasites were quantified and mounted for taxonomic identification and analysis of parasite communities. The P. squamosissimus specimens analyzed in this study had an average standard length of 25.21 ± 2.27 cm and average weight of 328.82 ± 89.03 g. We obtained, in total, 5227 specimens of metazoan parasites, with 2880 (55.1%) Diplectanum piscinarius (Monogenoidea: Diplectanidae) and 2347 (44.9%) metacercarie Austrodiplostomum compactum (Digenea, Diplostomidae), both with prevalence of 100% and abundance of 57.6 and 46.9, respectively. Also, we observed low parasite diversity (species richness = 2), Simpson index (D) of 0.505 and low values of the indices of Shannon (H '= 0.688) and diversity of Margalef (I = 0.177). The Berger-Parker dominance index (p = 0.551) indicated a slight dominance of the monogenean D. piscinarius. There was a positive correlation assessed by Pearson coefficient between parasite abundance of D. piscinarius and standard length (r = 0.43) and weight (r = 0.51) of hosts